The Role of Cost Structure in Decision Making: A Systematic Literature Review - Yuda Satria Nugraha (Penerbit Goodwood, 2025)
Purpose: This study explores how cost structure analysis supports managerial decisions, aiming to enhance strategic and relevant cost accounting practices across diverse business sectors. Methodology/approach: This research uses the Systematic Literature Review (SLR) method based on the PRISMA protocol. Literature was retrieved from the Scopus and Web of Science databases for the period 2015-2025, with a focus on articles that discuss the relationship between cost structure, accounting information, and managerial decision making. Results/findings: The review highlights diverse cost analysis approaches—ABC, TDABC, optimization, and environmental modeling—that support strategic decisions. Despite benefits in pricing and resource allocation, challenges like data inconsistency and system complexity persist. Findings stress the importance of adaptable, integrated systems for effective cost management in dynamic environments. Conclusion: This study highlights the strategic role of cost structure analysis in managerial decision-making, supporting pricing, planning, and resource efficiency. Despite varied approaches like ABC and TDABC, challenges persist, data inconsistency, complexity, and limited organizational capacity. The findings stress the need for adaptive, tech-driven cost systems. Limitations: This study is limited to ten articles from Scopus and WoS, potentially restricting generalizability across industries, regions, and evolving cost structure practices. Future research should explore broader sectors to enhance the relevance and applicability of cost analysis in dynamic business environments. Contribution: This study contributes to managerial accounting by guiding practitioners, researchers, and educators in enhancing cost structure analysis for strategic decision-making across various industries.